Dialectical movements with the Toba people in the Argentine Chaco. Issue 2 (3rd April 2019) - Citro, Silvia
ABSTRACT: Since 1998, I have undertaken fieldwork with the Indigenous peoples of the Argentine Chaco, focusing initially on their dances and embodied practices. After this ethnographic research, I began to think more deeply about the relationships between fieldwork and reflexivity and the possibilities of redefining analytical categories in the global South. The purpose of this article is to revisit my emphasis on a 'dialectical approach to embodiment' as a starting point for analysing cultural transformation in Latin America. I argue that this methodological approach has been closely linked to the interweaving of conflicting embodied experiences and peripheral geopolitical locations. In this regard I analyse how the contradictory experiences identified in my fieldwork with the Toba people, and also in my intersubjective and geopolitical positions as a Latin American academic woman, led me to a critical re-examination of dialectics. Further, I describe how this methodological approach, while well received among Latin American scholars has to some degree been resisted by (North) American and British scholars, and I explore the geopolitical implications of these disparate academic positions. Through these critical movements, I hope to contribute to rethinking dialectics in postcolonial contexts, adding some embodied voices from the Latin American South.